Four-fold symmetry of resistivity and flux pinning energy in Ba0.67K0.33BiO3+δ single crystal. (2nd November 2016) - Wu, Z F; Tao, J; Xu, X B; Qiu, L; Yang, S G; Wang, Z H
Abstract: Ba0.67 K0.33 BiO3+ δ single crystal with T c ∼ 26.4 K has been prepared by the molten salt electrochemical method. We observed a four-fold symmetry in the angular dependence of ab -plane resistance R ( θ ) at H = 0.5 T and T = 25.5 K for the first time. The data can be scaled by R = [ R 1 sin 2 ( θ + 45°) + R 2 cos 2 ( θ + 45°) − R (90°)]|sin2 θ | + R (90°). Although dip structure appears in R ( θ ) when the angles between the magnetic field direction and c -axis are 0°, 90°, 180° and 270°, respectively, the maximal position of resistance tilted away θ = 45° and θ = 135°, namely the angle difference between two peaks is 79° or 101°. This result indicates the superconducting Ba0.67 K0.33 BiO3+ δ single crystal is probably an orthorhombic structure with distorted Bi−O octahedron. We consider that the angular dependence of resistivity comes from the superconducting energy gap with d x 2 − y 2 pairing symmetry. The flux pinning energy for θ = 90° is higher than that for θ = 135° proves the existence of the anisotropic vortex pinning effect. The field dependence of flux pinning energy displays a power law, U ∝ H − α . The irreversibility line was also discussed.